Amine-functionalized poly (arylene sulfide) polymers
By introducing specific repeating unit combinations into poly(arylene sulfide) polymers, the problem that the polymer cannot maintain a melting state at curing temperature is solved, and good blending and blending capabilities in the coating are achieved, and the Mechanical characteristics, reactivity and low melting point requirements.
Patent Information
- Application Number
- CN202380049545.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-27
- Filing Date
- 2023-04-04
- Publication Date
- 2025-02-18
AI Technical Summary
The existing poly(arylene sulfide) polymers cannot maintain a melting state at curing temperatures, resulting in limited ability to blend and blend in coatings and difficult to meet sufficient mechanical properties, reactivity and low melting point requirements at the same time.
By introducing a specific combination of repeat units into the poly(arylene sulfide) polymer, including 85.0% to 97.0 mole% repeat units (RPASp), 2.5% to 10.0 mole% repeat units (RPASo/m), and 0.5 % to 5.0 mole% repeat units (RPASn) to achieve appropriate functionalization, acceptable molecular weight range and low melting point.
The polymer is maintained in a molten state at the curing temperature, which enhances the blending and blending capabilities in the coating, while ensuring mechanical characteristics and reactivity, meeting the needs of heat and chemical resistance.
Smart Images

Figure BDA0005206254830000081 
Figure BDA0005206254830000091 
Figure BDA0005206254830000092
Abstract
Description
[0001] Citation of Related Applications
[0002] This application claims priority to U.S. Provisional Application No. 63 / 335,254, filed on April 27, 2022, the entire contents of which are incorporated by reference into this application for all purposes. Technical Field
[0003] The present invention relates to an amine-functionalized poly(arylene sulfide) polymer, to a process for its manufacture and to a composition comprising said polymer, and to the use of said composition for coatings, in particular for heat-resistant and chemical-resistant coatings for use in chemical process pipes or in the oil and gas sector. Background Art
[0004] Poly(arylene sulfide) (PAS) polymers, including polyphenylene sulfide (PPS) polymers, are well-known polymers having excellent properties suitable for use in engineering plastics, such as heat resistance, chemical resistance, electrical insulation, moldability, and mechanical properties.
[0005] PPS (typically PAS) has a T ranging from 85°C to 100°C. g and a melting temperature (T m ). PPS polymers are usually formed by the reaction of sodium sulfide (Na2S) or sodium hydrosulfide (NaSH) with p-dichlorobenzene in a polar solvent.
[0006] Amine-functionalized PAS polymers, i.e., PAS containing at least one amine as a terminal or pendant group in the backbone, are also known and have been proposed for various functionalities and advantageous properties, particularly with respect to their ability to bond to impact modifiers, binders or fillers.
[0007] Processes for introducing amine groups into PAS copolymers by copolymerizing dihaloaromatic compounds with dichloroaniline are known, notably from JP3599124 and JP3779336.
[0008] In these documents, the dihaloaromatic compound is preferably p-dichlorobenzene, thus producing a PPS-type poly(arylene sulfide), although small amounts (up to 20 mole %) of additional dihaloaromatic compounds (notably including m-dichlorobenzene and o-dichlorobenzene) are taught to be potentially tolerated.
[0009] PAS have thermal and chemical resistance, which may make them particularly suitable for use in applications that expose them to hydrocarbon fluids (especially at high temperatures), such as for conveying corrosive fluids in chemical processing pipelines; and for the transportation of oil and gas, such as in the development of deep reservoirs.
[0010] Certain classes of coatings used in the chemical industry and / or in oil and gas recovery, such as coatings based on fusion bonded epoxies, have a cure temperature of no more than 260° C. As noted, PAS can bring valuable properties to such coatings; however, in order to incorporate PAS into such cured coatings, the PAS would require both reactive functionality (such as an amine) and a melting temperature below 260° C. PAS having such advantageous characteristics at the same time would be in a molten state at the cure temperature, i.e., in a state that facilitates incorporation and blending, and would likely react with the bulk polymer matrix of the coating, thereby forming a chemically bonded interpenetrating network with the bulk polymer matrix of the coating.
[0011] Therefore, there is a need in the art for a PAS polymer having a compromise of properties, namely a molecular weight to ensure adequate mechanical properties, sufficient amine functionalization for adequate reactivity toward epoxy resins, and a melting point of no more than about 260° C. to enable reaction in the molten state in a liquid epoxy resin during its cure.
[0012] Furthermore, there is a need in the art for a method of making such PAS polymers in an efficient and simple manner that provides access to polymers with significant amine functionalization while avoiding tedious post-functionalization techniques. Summary of the invention
[0013] In a first aspect, the present invention relates to a poly(arylene sulfide) polymer [polymer (PAS)] having a weight average molecular weight of at least 24,000 as determined by gel permeation chromatography, the polymer (PAS) comprising:
[0014] - a repeating unit represented by the following formula (R PASp ):
[0015] [-Ar p -S-](R PASp )
[0016] in
[0017] -Ar p -yes
[0018] The amount thereof is 85.0% to 97.0% by mole;
[0019] - a repeating unit represented by the following formula (R PASo / m ):
[0020] [-Ar o / m -S-](R PASo / m )
[0021] in
[0022] -Ar p / m -yes Any one of, in an amount of 2.5% to 10.0% by mole; and
[0023] - a repeating unit represented by the following formula (R PASn ):
[0024] [-Ar n -S-](R PASn )
[0025] in
[0026] -Ar n -yes
[0027] The amount is 0.5% to 5.0% by mole,
[0028] in:
[0029] - mol% is determined relative to the total number of moles of repeating units of the polymer (PAS);
[0030] -R is independently selected in each case from the group consisting of: C1-C 12 Alkyl, C7-C 24 Alkyl aryl, C7-C 24 Arylalkyl, C6-C 24 Arylene and C6-C 18 aryloxy;
[0031] - i is in each case an independently selected integer from 0 to 4;
[0032] j is in each case an independently selected integer from 0 to 3.
[0033] In all of the above formulae (a1) to (a4), the dashed bond symbol (...) is used to indicate the connection to the sulfur atom to the adjacent repeat unit.
[0034] The polymer of the present invention (PAS) advantageously possesses a combination of properties that make it suitable for use in combination with fusion bonded epoxy resins, namely good mechanical properties, high reactivity and a low melting point, particularly at the curing temperature of the fusion bonded epoxy resin (below a T of about 260°C). m ) can reach the molten state.
[0035] In a second aspect, the present invention relates to a process for the manufacture of a poly(arylene sulfide) polymer, in particular for the manufacture of a polymer (PAS) as described above in detail, said process comprising reacting a monomer mixture comprising:
[0036] - from 85.0% to 97.0% by mole of at least one compound having the formula X-Ar p -X', wherein -Ar p -yes
[0037] - from 2.5% to 10.0% by mole of at least one second dihalogenated compound of the formula: X"-Ar o / m -X"', where -Ar o / m -yes Any one of
[0038] - from 2.5 to 5.0 mol% of at least one third dihalogenated compound having the formula: X' v -Ar n -X v , where -Ar n -yes
[0039] in:
[0040] -X、X'、X”、X”'、X' v and X v each of which is an independently selected halogen, preferably chlorine or bromine, more preferably chlorine;
[0041] -R is independently selected in each case from the group consisting of: C1-C 12 Alkyl, C7-C 24 Alkyl aryl, C7-C 24 Arylalkyl, C6-C 24 Arylene and C6-C 18 aryloxy;
[0042] - i is in each case an independently selected integer from 0 to 4;
[0043] -j is in each case an independently selected integer from 0 to 3.
[0044] In a third aspect, the present invention relates to a composition (C) comprising:
[0045] - a polymer as described above (PAS), and
[0046] - At least one epoxy resin.
[0047] The Applicant has found that by combining the repeating units (R PASp ), repeating unit (R PASo / m ) and repeating units (R PASn ), which can achieve an optimal balance of properties, including appropriate functionalization, an acceptable molecular weight range and a moderate melting point that promotes the melting-in of the polymer (PAS) in different curable coating applications. DETAILED DESCRIPTION
[0048] In the present application, any description even if described with respect to a specific embodiment is applicable to other embodiments of the present disclosure and may be interchangeable therewith.
[0049] In the present application, where an element or component is said to be included in and / or selected from a list of multiple elements or components listed, it should be understood that in the relevant embodiments explicitly considered herein, the element or component may also be any one of these individually listed elements or components, or may also be selected from a group consisting of any two or more of these explicitly listed elements or components; any element or component listed in the list of elements or components may be omitted from this list.
[0050] Throughout this application, any recitation of numerical ranges by endpoints herein includes all numbers subsumed within the recited range as well as the endpoints of said range and equivalents thereof.
[0051] Poly(arylene sulfide) polymer [Polymer (PAS)]
[0052] As stated, the poly(arylene sulfide) polymer [polymer (PAS)] comprises:
[0053] - a repeating unit (R) in an amount of 85.0 to 97.0 mol% PASp );
[0054] - a repeating unit (R) in an amount of 2.5 to 10.0 mol% PASo / m );as well as
[0055] - a repeating unit (R) in an amount of 0.5 to 5.0 mol% PASn ),
[0056] The mole % is determined relative to the total moles of repeating units of the polymer (PAS).
[0057] When the repeating unit (R PASo / m) below 2.5 mol %, the polymer (PAS) will not be optimized, particularly because the melting point will be too high for the polymer (PAS) to be usable in certain curable coating compositions (e.g., in molten epoxy resin solutions).
[0058] On the other hand, more than 10.0 mol% of the repeating units (R PASo / m ) will adversely affect the ability of the polymer (PAS) to reach a reasonable molecular weight, thus generally compromising the performance of mechanical properties.
[0059] The polymer (PAS) may further comprise a repeating unit (R PASt ):
[0060] [-Ar t -S-](R PASt )
[0061] Among them -Ar t -yes
[0062] in:
[0063] -R is independently selected in each case from the group consisting of: C1-C 12 Alkyl, C7-C 24 Alkyl aryl, C7-C 24 Arylalkyl, C6-C 24 Arylene and C6-C 18 aryloxy;
[0064] - k is in each case an independently selected integer from 0 to 3;
[0065] -m is 1 or 0 in each case.
[0066] In formula a5), the bond symbol It is intended to represent a repeating unit (R PASp )、(R PASo / m ), and / or (R PASn ) sequence of polymer chains.
[0067] Therefore, the polymer (PAS) of the present invention comprises:
[0068] - a repeating unit (R) in an amount of 85.0 to 97.0 mol% PASp );
[0069] - a repeating unit (R) in an amount of 2.5 to 10.0 mol% PASo / m );
[0070] - a repeating unit (R) in an amount of 0.5 to 5.0 mol% PASn);as well as,
[0071] - Optionally, the repeating unit (R PASt )
[0072] The mole % is determined relative to the total moles of repeating units of the polymer (PAS).
[0073] Preferably, the polymer (PAS) of the present invention comprises:
[0074] - a repeating unit (R) in an amount of 88.0% to 96.0% by mole PASp );
[0075] - a repeating unit (R) in an amount of 3.0 to 8.0 mol% PASo / m );
[0076] - a repeating unit (R) in an amount of 1.0 to 4.0 mol% PASn );as well as,
[0077] - Optionally, the repeating unit (R PASt ), wherein the mole % is determined relative to the total moles of repeating units of the polymer (PAS).
[0078] More preferably, the polymer (PAS) of the present invention comprises:
[0079] - a repeating unit (R) in an amount of 89.0% to 94.5% by mole PASp );
[0080] - a repeating unit (R) in an amount of 4.0 to 7.5 mol% PASo / m );
[0081] - a repeating unit (R) in an amount of 1.5 to 3.5 mol% PASn );as well as,
[0082] - Optionally, the repeating unit (R PASt ),
[0083] The mole % is determined relative to the total moles of repeating units of the polymer (PAS).
[0084] According to certain embodiments, the polymer (PAS) actually comprises repeating units (R PASt ).
[0085] According to these embodiments, the polymer of the present invention (PAS) comprises:
[0086] - a repeating unit (R) in an amount of 85.0% to 96.8% by mole PASp);
[0087] - a repeating unit (R) in an amount of 2.5 to 10.0 mol% PASo / m );
[0088] - a repeating unit (R) in an amount of 0.5 to 5.0 mol% PASn );as well as,
[0089] - a repeating unit (R) in an amount of 0.2 to 3.0 mol% PASt )
[0090] The mole % is determined relative to the total moles of repeating units of the polymer (PAS).
[0091] Preferably, the polymer (PAS) of the present invention comprises:
[0092] - a repeating unit (R) in an amount of 88.0% to 95.7% by mole PASp );
[0093] - a repeating unit (R) in an amount of 3.0 to 8.0 mol% PASo / m );
[0094] - a repeating unit (R) in an amount of 1.0 to 4.0 mol% PASn );as well as,
[0095] - a repeating unit (R) in an amount of 0.3 to 2.0 mol% PASt ), wherein the mole % is determined relative to the total moles of repeating units of the polymer (PAS).
[0096] More preferably, the polymer (PAS) of the present invention comprises:
[0097] - a repeating unit (R) in an amount of 89.0% to 94.0% by mole PASp );
[0098] - a repeating unit (R) in an amount of 4.0 to 7.5 mol% PASo / m );
[0099] - a repeating unit (R) in an amount of 1.5 to 3.5 mol% PASn );as well as,
[0100] - a repeating unit (R) in an amount of 0.5 to 1.5 mol% PASt ),
[0101] The mole % is determined relative to the total moles of repeating units of the polymer (PAS).
[0102] According to an embodiment of the present invention, the polymer (PAS) consists of or essentially consists of: a repeating unit (R PASp )、(R PASo / m )、(R PASn ) and optionally (R PASt As described, according to certain other embodiments, the polymer (PAS) consists of or consists essentially of: a repeating unit (R PASp )、(R PASo / m )、(R PASn ) and (R PASt ). The expression "consisting essentially of" when used in conjunction with the repeating units of the polymer (PAS) is intended to mean that small amounts of stray repeating units can be tolerated to the extent that they do not significantly change the favorable properties of the polymer (PAS). Amounts of less than 1 mol% are generally considered not to significantly affect the properties of the polymer (PAS).
[0103] The repeating unit (R) of the polymer (PAS) PASp ) is preferably a repeating unit having the formula (R PPSp ):
[0104]
[0105] Similarly, the repeating unit (R PASo / m ) is preferably selected from repeating units having the formula (R PPSo ) and (R PPSm ) group:
[0106]
[0107] In addition, the repeating unit (R PASn ) is preferably of formula (R PPSn,o )(R PPSn,m )(R PPSn,p ) in any of the repeating units (R PPSn ):
[0108]
[0109] The repeating units as detailed above are units derived from the polycondensation reaction of dihaloaniline, in particular from dichloroaniline.
[0110] Most preferably, the repeating unit (R PASn ) is a compound having the formula (R PPS_TCA )'s repeating unit:
[0111]
[0112] In addition, the repeating unit (R PASt ) preferably has the formula: The repeating unit (R PPSt ), wherein m is 0 or 1, preferably m is 0.
[0113] Therefore, the polymer (PAS) of the present invention is preferably a polyphenylene sulfide polymer [polymer (PPS)] comprising:
[0114] - a repeating unit (R) in an amount of 85.0 to 97.0 mol% PPSp );
[0115] -Repeating unit (R PPSo ) and / or repeating units (R PPSm ), repeating unit (R PPSo ) and repeating units (R PPSm ) is 2.5% to 10.0% by mole;
[0116] - a repeating unit (R) in an amount of 0.5 to 5.0 mol% PPSn );as well as,
[0117] - Optionally, the repeating unit (R PPSt )
[0118] The mole % is determined relative to the total moles of repeating units of the polymer (PPS).
[0119] Preferably, the polymer (PPS) of the present invention comprises:
[0120] - a repeating unit (R) in an amount of 88.0% to 96.0% by mole PPSp );
[0121] -Repeating unit (R PPSo ) and / or repeating units (R PPSm ), repeating unit (R PPSo ) and repeating units (R PPSm ) is 3.0% to 8.0% by mole;
[0122] - a repeating unit (R) in an amount of 1.0 to 4.0 mol% PPSn );as well as,
[0123] - Optionally, the repeating unit (R PASt ), wherein the mole % is determined relative to the total moles of repeating units of the polymer (PPS).
[0124] More preferably, the polymer (PAS) of the present invention comprises:
[0125] - a repeating unit (R) in an amount of 89.0% to 94.5% by mole PPSp );
[0126] -Repeating unit (R PPSo ) and / or repeating units (R PPSm ), repeating unit (R PPSo ) and repeating units (R PPSm ) is 4.0% to 7.5% by mole;
[0127] - a repeating unit (R) in an amount of 1.5 to 3.5 mol% PPSn );as well as,
[0128] - Optionally, the repeating unit (R PPSt )
[0129] The mole % is determined relative to the total moles of repeating units of the polymer (PPS).
[0130] According to certain embodiments, the polymer (PAS) is preferably a polyphenylene sulfide polymer [polymer (PPS)] comprising:
[0131] - a repeating unit (R) in an amount of 85.0% to 96.8% by mole PPSp );
[0132] -Repeating unit (R PPSo ) and / or repeating units (R PPSm ), repeating unit (R PPSo ) and repeating units (R PPSm ) is 2.5% to 10.0% by mole;
[0133] - a repeating unit (R) in an amount of 0.5 to 5.0 mol% PPSn );as well as,
[0134] - a repeating unit (R) in an amount of 0.2 to 3.0 mol% PPSt )
[0135] The mole % is determined relative to the total moles of repeating units of the polymer (PPS).
[0136] Preferably, the polymer (PPS) of these embodiments comprises:
[0137] - a repeating unit (R) in an amount of 88.0% to 95.7% by mole PPSp );
[0138] -Repeating unit (R PPSo ) and / or repeating units (R PPSm), repeating unit (R PPSo ) and repeating units (R PPSm ) is 3.0% to 8.0% by mole;
[0139] - a repeating unit (R) in an amount of 1.0 to 4.0 mol% PPSn );as well as,
[0140] - a repeating unit (R) in an amount of 0.3 to 2.0 mol% PASt ), wherein the mole % is determined relative to the total moles of repeating units of the polymer (PPS).
[0141] More preferably, the polymer (PAS) of these embodiments comprises:
[0142] - a repeating unit (R) in an amount of 89.0% to 94.0% by mole PPSp );
[0143] -Repeating unit (R PPSo ) and / or repeating units (R PPSm ), repeating unit (R PPSo ) and repeating units (R PPSm ) is 4.0% to 7.5% by mole;
[0144] - a repeating unit (R) in an amount of 1.5 to 3.5 mol% PPSn );as well as,
[0145] - a repeating unit (R) in an amount of 0.5 to 1.5 mol% PPSt )
[0146] The mole % is determined relative to the total moles of repeating units of the polymer (PPS).
[0147] Most preferably, in all the above listed and preferred polymers (PPS), the repeating units (R PPSn ) is a compound having the formula (R PPS_TCA ) unit.
[0148] Preferably, the polymer (PAS) has a weight average molecular weight (Mw) of at least 25,000 g / mol, more preferably at least 26,000 g / mol, even more preferably at least 27,000 g / mol, as determined by gel permeation chromatography.
[0149] Preferably, the polymer (PAS) has a weight average molecular weight (MW) of at most 120,000 g / mol, more preferably at most 110,000 g / mol, even more preferably at most 100,000 g / mol, yet more preferably at most 90,000 g / mol, as determined by gel permeation chromatography.w ).
[0150] Preferably, the polymer (PAS) has a melting point (T ) of at least 230° C., more preferably at least 235° C., even more preferably at least 240° C., when determined in a differential scanning calorimeter (DSC) at the 2nd thermal scan according to ASTM D3418 using a heating and cooling rate of 20° C. / min. m ).
[0151] Preferably, the polymer (PAS) has a melting point (T ) of at most 265° C., more preferably at most 264° C., even more preferably at most 263° C., when determined in a differential scanning calorimeter (DSC) at the 2nd thermal scan according to ASTM D3418 using a heating and cooling rate of 20° C. / min. m ).
[0152] The polymer (PAS) may advantageously comprise at least one functional group at at least one of its chain ends. For example, the polymer (PAS) may have a functional group at each end of its chain.
[0153] When present, the functional group is according to the following formula (I):
[0154]
[0155] wherein Z is selected from the group consisting of halogen atoms (e.g., chlorine), carboxyl groups, amino groups, hydroxyl groups, thiol groups, anhydride groups, isocyanate groups, amide groups, and derivatives thereof, such as salts of sodium, lithium, potassium, calcium, magnesium, and zinc.
[0156] Preferably, when present, the functional group is selected from the group consisting of an amino group, a hydroxyl group, a thiol group, a hydroxylate and a thiolate.
[0157] Such end groups may be suitably introduced into the polymer (PAS) of the present invention by using suitable monohalogenated functional compounds during the manufacture of the polymer (PAS) itself and / or by appropriate chemistry at the end groups.
[0158] Process for making poly(arylene sulfide) polymers
[0159] As mentioned, in a second aspect, the present invention relates to a process for the manufacture of a poly(arylene sulfide) polymer, in particular for the manufacture of a polymer (PAS) as described above in detail. The process comprises reacting a dihalogenated compound X-Ar as described above in the presence of at least one sulfur compound [compound (SC)] p -X', X"-Ar o / m -X' and X' v -Ar n -Xv The mixture reacts.
[0160] Possibly, the mixture further comprises at least one trihalogenated compound of formula (II):
[0161] in:
[0162] -R is independently selected in each case from the group consisting of: C1-C 12 Alkyl, C7-C 24 Alkyl aryl, C7-C 24 Arylalkyl, C6-C 24 Arylene and C6-C 18 aryloxy;
[0163] - k is in each case an independently selected integer from 0 to 3;
[0164] - m is in each case 1 or 0, preferably m is 0;
[0165] -X 1 , X 2 and X 3 Each of is an independently selected halogen, preferably chlorine or bromine, more preferably chlorine.
[0166] As described above, the dihalogenated compound X-Ar p -X', X"-Ar o / m -X' and X' v -Ar n -X v , and optionally the amount of the trihalogenated compound of formula (II) corresponds to the corresponding repeating unit (R PASp )、(R PASo / m )、(R PASn ) and, where appropriate (R PASt ) target amounts, which target amounts have been described above for the binding polymer (PAS).
[0167] Thus, as stated, the monomer mixture comprises:
[0168] - a dihalogenated compound X-Ar in an amount of 85.0% to 97.0% by mole p -X';
[0169] - a dihalogenated compound X"-Ar in an amount of 2.5% to 10.0% by mole o / m -X"'; and
[0170] - dihalogenated compound X' in an amount of 0.5% to 5.0% by mole v -Ar n -Xv ,
[0171] The mole % is determined relative to the total moles of the compound in the monomer mixture.
[0172] In particular, the monomer mixture comprises:
[0173] - a dihalogenated compound X-Ar in an amount of 85.0% to 97.0% by mole p -X';
[0174] - a dihalogenated compound X"-Ar in an amount of 2.5% to 10.0% by mole o / m -X"';
[0175] - dihalogenated compound X' in an amount of 0.5% to 5.0% by mole v -Ar n -X v ;as well as,
[0176] - Optionally, a trihalogenated compound of formula (II) in an amount of 0 to 3.0 mol % wherein the mol % is determined relative to the total number of moles of the compound in the monomer mixture.
[0177] Preferably, the monomer mixture comprises:
[0178] - a dihalogenated compound X-Ar in an amount of 88.0% to 96.0% by mole p -X';
[0179] - a dihalogenated compound X"-Ar in an amount of 3.0% to 8.0% by mole o / m -X"';
[0180] - a dihalogenated compound X' in an amount of 1.0% to 4.0% by mole v -Ar n -X v ;as well as,
[0181] - Optionally, a trihalogenated compound of formula (II) in an amount of 0 to 2.0 mol %, wherein the mol % is determined relative to the total number of moles of the compound in the monomer mixture.
[0182] More preferably, the monomer mixture comprises:
[0183] - a dihalogenated compound X-Ar in an amount of 89.0% to 94.5% by mole p -X';
[0184] - a dihalogenated compound X"-Ar in an amount of 4.0% to 7.5% by mole o / m -X"';
[0185] - dihalogenated compound X' in an amount of 1.5% to 3.5% by mole v -Ar n -X v ;as well as,
[0186] - optionally, a trihalogenated compound of formula (II) in an amount of 0 to 1.5 mol%,
[0187] The mole % is determined relative to the total moles of the compound in the monomer mixture.
[0188] Whereas the polymer (PAS) actually comprises repeating units (R PASt ) embodiment, the monomer mixture comprises:
[0189] - a dihalogenated compound X-Ar in an amount of 85.0% to 96.8% by mole p -X';
[0190] - a dihalogenated compound X"-Ar in an amount of 2.5% to 10.0% by mole o / m -X"';
[0191] - dihalogenated compound X' in an amount of 0.5% to 5.0% by mole v -Ar n -X v ;as well as,
[0192] - a trihalogenated compound of formula (II) in an amount of 0.2% to 3.0% by mole
[0193] The mole % is determined relative to the total moles of the compound in the monomer mixture.
[0194] Preferably, the monomer mixture according to these embodiments comprises:
[0195] - a dihalogenated compound X-Ar in an amount of 88.0% to 95.7% by mole p -X';
[0196] - a dihalogenated compound X"-Ar in an amount of 3.0% to 8.0% by mole o / m -X"';
[0197] - a dihalogenated compound X' in an amount of 1.0% to 4.0% by mole v -Ar n -X v ;as well as,
[0198] - a trihalogenated compound of formula (II) in an amount of 0.3% to 2.0% by mole
[0199] The mole % is determined relative to the total moles of the compound in the monomer mixture.
[0200] More preferably, the monomer mixture according to these embodiments comprises:
[0201] - a dihalogenated compound X-Ar in an amount of 89.0% to 94.0% by mole p -X';
[0202] - a dihalogenated compound X"-Ar in an amount of 4.0 to 8.0 mol% o / m -X"';
[0203] - dihalogenated compound X' in an amount of 1.5% to 4.0% by mole v -Ar n -X v ;as well as,
[0204] - a trihalogenated compound of formula (II) in an amount of 0.5% to 1.5% by mole
[0205] The mole % is determined relative to the total moles of the compound in the monomer mixture.
[0206] In all the embodiments listed above, the compound having the formula X-Ar p The first dihalogenated compound of -X' is preferably p-dihalobenzene, more preferably p-dichlorobenzene.
[0207] In all of the embodiments listed above, the compound having the formula X"-Ar o / m The second dihalogenated compound of -X'' is preferably selected from the group consisting of o-dihalobenzene and m-dihalobenzene; and more preferably selected from the group consisting of o-dichlorobenzene and m-dichlorobenzene.
[0208] In all the embodiments listed above, the compound has the formula: X' v -Ar n -X v The third dihalogenated compound is preferably a dihalogenated aniline, and is preferably selected from the group consisting of 3,5-dichloroaniline, 2,5-dichloroaniline and 2,6-dichloroaniline, wherein 3,5-dichloroaniline is preferred.
[0209] In all the embodiments listed above, the trihalogenated compound having formula (II) is preferably a trihalobenzene, more preferably 1,2,4-trichlorobenzene.
[0210] The sulfur compound (SC) used in the method of the present invention is selected from the group consisting of thiosulfate, thiourea, thioamide, elemental sulfur, thiocarbamate, metal disulfide and oxysulfide, thiocarbonate, organic mercaptan, organic mercaptan salt, organic sulfide, alkali metal sulfide and disulfide and hydrogen sulfide. Preferably, the sulfur compound is an alkali metal sulfide. In certain embodiments, the alkali metal sulfide is produced in situ by alkali metal hydrosulfide and alkali metal hydroxide. For example, Na2S is a particularly desirable alkali metal sulfide, which can be advantageously used as a sulfur compound (SC). Na2S can be produced in situ by NaSH and NaOH.
[0211] The polymerization solvent is selected so that it is a solvent for the reaction components at the reaction temperature (discussed below). In some embodiments, the polymerization solvent is a polar aprotic solvent. Examples of desired polar aprotic solvents include, but are not limited to, hexamethylphosphoramide, tetramethylurea, N,N-ethylenedipyrrolidone, N-methyl-2-pyrrolidone ("NMP"), pyrrolidone, caprolactam, N-ethylcaprolactam, cyclopentane, N,N'-dimethylacetamide and 1,3-dimethyl-2-imidazolidinone. Preferably, the polymerization solvent is NMP. In embodiments where the polymerization solvent includes NMP, NMP can react with NaOH to form N-methyl-1,4-aminobutyrate ("SMAB").
[0212] In some embodiments, the reaction components further include a molecular weight regulator. Relative to a synthesis scheme that does not include a molecular weight regulator, the molecular weight regulator can help increase the molecular weight of the polymer (PAS). Preferably, the molecular weight regulator is an alkali metal carboxylate. The alkali metal carboxylate is represented by the following formula: R'CO2M', wherein R' is selected from C1 to C 20 Hydrocarbon, C1 to C 20 and M' is selected from the group consisting of lithium, sodium, potassium, rubidium or cesium. Preferably, M' is sodium or potassium, most preferably sodium. Preferably, the alkali metal carboxylate is sodium acetate.
[0213] The process of the invention advantageously comprises subjecting a dihalogenated compound X-Ar p -X', X"-Ar o / m -X' and X' v -Ar n -X v and optionally a monomer mixture of a trihalogenated compound of formula (II) as described in detail above at a reaction temperature selected so that X-Ar p -X', X"-Ar o / m -X' and X' v -Ar n -Xv And optionally there is the trihalogenated compound of formula (II) and SC polymerization to form polymer (PAS). In certain embodiments, the temperature of making monomer mixture react is from 170 ℃ to 450 ℃ or from 200 ℃ to 285 ℃ scope. The reaction time (also known as the duration of polymerization reaction) can be from 10 minutes to 3 days or from 1 hour to 8 hours. In the method of the present invention, during the reaction, it is advantageous to select pressure (reaction pressure) to maintain monomer mixture and solvent (when used) in liquid phase. In certain embodiments, reaction pressure can be from 0 pounds per square inch gauge pressure (" psig ") to 400psig, from 30psig to 300psig or from 100psig to 250psig.
[0214] The step of reacting the monomer mixture can be terminated by cooling the product mixture to a temperature at which the polymerization reaction stops. "Product mixture" refers to a mixture formed during the reaction, and contains any remaining unreacted monomer mixture components, the polymer (PAS) formed, and any reaction byproducts. Cooling can be performed using a variety of techniques known in the art. In some embodiments, cooling can be performed by flashing the reaction mixture rapidly. In some embodiments, cooling can include liquid quenching. In liquid quenching, a quenching liquid is added to the reaction mixture to cool the product mixture. In some embodiments, the quenching liquid is selected from the group consisting of a polymerization solvent, water, and a combination thereof. In some embodiments, the temperature of the quenching liquid can be from about 15°C to 99°C. In some embodiments, the temperature of the quenching liquid can be from 54°C to 100°C (for example, in an embodiment in which the quenching liquid is a solvent) or from 15°C to 32°C (for example, in an embodiment in which the quenching liquid is water). Cooling can be further facilitated by using a reactor jacket or coil to cool the reaction vessel ("polymerization reactor") in which the polymerization reaction is performed. For clarity, the termination of the polymerization reaction does not mean the complete reaction of the reaction components. Typically, termination is initiated when the polymerization reaction is substantially complete or a target yield is achieved or when further reaction of the reaction components will not result in a significant increase in the average molecular weight of the polymer (PAS).
[0215] After termination, the polymer (PAS) is usually present in the product mixture as an admixture. The product mixture usually further includes water, solvents, reaction byproducts including salts (e.g., sodium chloride and sodium acetate); oligomers and any unreacted reaction components (collectively referred to as "reaction post-compounds"). Typically, after termination, the product mixture including the polymer (PAS) exists as a slurry having a liquid phase and a solid phase containing the polymer (PAS) (precipitated from the solvent during liquid quenching or during flash evaporation). In some embodiments, for example, by filtering the slurry after termination, the product mixture including the polymer (PAS) can be provided as a wet polymer (PAS).
[0216] After termination, a recovery process may be implemented. The recovery process comprises one or more washes, wherein each wash comprises contacting the polymer (PAS) formed during the polymerization reaction with a liquid. The liquid of each wash is independently selected from water, an acid aqueous solution and an aqueous solution of a metal cation.
[0217] After the recovery process, the polymer (PAS) can be dried. Drying can be carried out at any temperature that can make the polymer (PAS) substantially dry, to obtain a dried polymer (PAS). Desirably, the drying process is selected to help prevent the oxidative curing of the polymer (PAS). For example, if the drying process is carried out at a temperature of at least 100 ° C, the drying can be carried out in a substantially non-oxidizing atmosphere (e.g., in a substantially oxygen-free atmosphere or under a pressure less than atmospheric pressure, for example, under vacuum). When the drying process is carried out at a temperature less than 100 ° C, the drying process can be promoted by drying under a pressure less than atmospheric pressure, so that the liquid component can be evaporated from the polymer (PAS). When drying is carried out at a temperature less than 100 ° C, the presence of a gaseous oxidizing atmosphere (e.g., air) does not usually result in detectable curing of the polymer (PAS).
[0218] Composition (C) and method for producing the same
[0219] As already stated, the present invention also relates to a composition (C) comprising a polymer (PAS) as described above and at least one epoxy resin.
[0220] Suitable epoxy resin compositions used in composition (C) include, but are not limited to, epoxy ethers formed by reaction of epihalohydrins (such as epichlorohydrin) with polyphenols, typically and preferably in the presence of a base. Suitable polyphenols include, for example, catechol, hydroquinone, resorcinol, bis(4-hydroxyphenyl)-2,2-propane (bisphenol A), bis(4-hydroxyphenyl)-1,1-isobutane, bis(4-hydroxyphenyl)-1,1-ethane, bis(2-hydroxyphenyl)-methane, 4,4-dihydroxybenzophenone, 1,5-hydroxynaphthalene, etc. Bisphenol A and the diglycidyl ether of bisphenol A are preferred.
[0221] Suitable epoxy resin can also include the polyglycidyl ethers (polyglicydyl ether) of polyvalent alcohol.These compounds can be derived from polyvalent alcohol, such as ethylene glycol, propylene glycol, butylene glycol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, glycerine, trimethylolpropane, pentaerythritol etc.Other suitable epoxides or polyepoxides include the polyglycidyl esters of the polyvalent carboxylic acids formed by the reaction of epihalohydrin or other epoxy compositions with aliphatic or aromatic polycarboxylic acids (such as succinic acid, adipic acid, azelaic acid, sebacic acid, maleic acid, fumaric acid, phthalic acid, tetrahydrophthalic acid, hexahydrophthalic acid, trimellitic acid etc.).On the one hand, the unsaturated fatty acids of dimerization and the polymerization polycarboxylic acid reaction can also be made to produce the polyglycidyl esters of polycarboxylic acids.
[0222] In an embodiment, the epoxy resin suitable for use in composition (C) can be derived by oxidation of ethylenically unsaturated alicyclic compounds. Ethylenically unsaturated alicyclic compounds are epoxidized by reaction with oxygen, perbenzoic acid, acid-aldehyde monoperacetate, peracetic acid, and the like. Polyepoxides produced by such reactions are known to those skilled in the art and include, but are not limited to, epoxy salicylic acid ethers and esters.
[0223] In an embodiment, epoxy resin comprises epoxy novolac resin, and it obtains by the reaction of the condensation product of epihalohydrin and aldehyde and monohydric or polyhydric phenol.Example includes but is not limited to the reaction product of the condensation product of epihalohydrin and formaldehyde and various phenols (for example as phenol, cresol, xylenol, butyl methyl phenol, phenylphenol, bisphenol, naphthol, bisphenol A, bisphenol F etc.).
[0224] In an embodiment, composition (C) is a curable composition further comprising at least one curing agent. In an embodiment, the curing agent described herein helps to obtain a composition (C) having a curing time on the order of three minutes or less. The curing agent is generally selected to be compatible with the composition (C) and operates to cure the composition (C) only when melted at the temperature used to cure the composition (C).
[0225] Suitable curing agent can include dihydrazide prepared by the reaction of carboxylic acid ester and hydrazine hydrate.Such reaction is well known to those skilled in the art and produces such as carbodihydrazide, oxalic acid dihydrazide, malonic acid dihydrazide, ethylmalonic acid dihydrazide, succinic acid dihydrazide, glutaric acid dihydrazide, adipic acid dihydrazide, pimelic acid dihydrazide, sebacic acid dihydrazide, maleic acid dihydrazide, isophthalic acid dihydrazide, eicosanedioic acid dihydrazide, valine dihydrazide and mixture thereof.Wherein, adipic acid dihydrazide, sebacic acid dihydrazide, isophthalic acid dihydrazide, eicosanedioic acid dihydrazide, valine dihydrazide are preferred, and sebacic acid dihydrazide is particularly preferred.
[0226] The composition (C) may further comprise at least one additive, for example in an amount of less than 10 wt.%, selected from the group consisting of colorants, dyes, pigments, lubricants, plasticizers, flame retardants, nucleating agents, heat stabilizers, light stabilizers, antioxidants, processing aids, fluxes, electromagnetic absorbers and combinations thereof, wherein the wt.% is based on the total weight of the composition (C).
[0227] Composition (C) may also contain at least one filler different from the above additives. When present, the filler may be present in composition (C) in an amount of at least 5 wt.%, at least 10 wt.%, at least 15 wt.%, at least 20 wt.%, based on the total weight of composition (C).
[0228] According to various embodiments of the present invention, the at least one filler may be present in composition (C) in an amount of up to 60 wt.%, up to 55 wt.%, up to 50 wt.%, up to 45 wt.%, based on the total weight of the polymer composition (C).
[0229] According to various embodiments of the present invention, the at least one additional additive may be present in composition (C) in an amount less than 5 wt.%, less than 4 wt.%, less than 3 wt.%, less than 2 wt.%, or less than 1 wt.%, based on the total weight of composition (C).
[0230] The at least one filler may be selected from the group consisting of toughening agents and reinforcing agents.
[0231] The toughening agent is preferably selected from elastomers.In a preferred embodiment, the toughening agent is present in composition (C) in an amount of up to 30 wt.%, such as up to 25 wt.%, based on the total weight of composition (C).
[0232] The reinforcing agent may be selected from the group consisting of fiber reinforced fillers, particle reinforced fillers and mixtures thereof. Fiber reinforced fillers are considered herein to have a material having a length, a width and a thickness, wherein the average length is significantly greater than both the width and the thickness. In general, the fiber reinforced fillers have an aspect ratio (defined as the average ratio between the length and the largest of the width and the thickness) of at least 5, at least 10, at least 20 or at least 50.
[0233] Fiber-reinforcing fillers include glass fibers, carbon fibers or graphite fibers, and fibers formed from silicon carbide, alumina, titanium dioxide, boron, etc., and may include mixtures containing two or more such fibers. Non-fiber-reinforcing fillers notably include talc, mica, titanium dioxide, calcium carbonate, potassium titanate, silica, kaolin, chalk, alumina, mineral fillers, etc.
[0234] Preferably, the at least one filler is a fiber-reinforced filler. Among the fiber-reinforced fillers, glass fibers and carbon fibers are preferred. According to a preferred embodiment of the present invention, based on the total weight of the composition (C), the composition (C) comprises up to 60 wt.%, for example from 30 to 40 wt.% of glass fibers and / or carbon fibers.
[0235] According to certain embodiments, the composition (C) can be used to prepare a composite material solution.
[0236] According to certain embodiments, composition (C) is a powder coating composition. A powder coating composition is a fusible composition made of loose particles that melt when heat is applied to form a coating film. The powder can be applied using methods known to those skilled in the art, such as, for example, electrostatic spraying, and can be cured to a dry film thickness of about 200 to about 500 microns, preferably 300 to 400 microns.
[0237] Products and Applications
[0238] In an embodiment, the present invention provides a method for coating a substrate using the composition (C) as described in detail above.
[0239] The use of composition (C) makes it possible to combine the advantageous properties of epoxy resins and polymers (PAS), while achieving a homogeneous and interpenetrating coating network by curing the epoxy resin at a temperature at which the polymer (PAS) can react in the molten state.
[0240] Notably, powder coatings of the type described herein are used on oil and gas pipelines, ie, large diameter pipelines made of high-grade steel.
[0241] In an embodiment, the powder composition is preferably applied to the surface of a substrate, preferably a metal substrate, more preferably a high performance steel substrate. The powder composition is applied using methods known to those skilled in the art, such as, for example, electrostatic spraying. Prior to applying the powder coating, the substrate is typically and preferably degreased and shot blasted, preferably to a depth of about 50 μm to 70 μm.
[0242] In an embodiment, the method described herein includes applying the powder composition described above to a substrate and curing the composition on the substrate. In one aspect, the powder composition is applied to the substrate by conventional methods (such as, for example, electrostatic spraying). The coated substrate is then heated to allow the powder particles to melt and fuse, and the coating is subsequently cured at the same temperature.
[0243] Should the disclosure of any patents, patent applications, and publications incorporated herein by reference conflict with the description of the present application to the extent that it might render a term unclear, the present description shall take precedence.
[0244] The present invention will now be described with reference to the following examples, which are intended to be illustrative only and are not intended to limit the scope of the present invention.
[0245] Experimental Section
[0246] raw materials
[0247] 1-Methyl-2-pyrrolidone ("NMP") (>99.0%): obtained from Tokyo Chemical Industry Co., Ltd. (TCI)
[0248] Sodium hydrosulfide ("NaSH") (55-60 wt.%): obtained from Akzo Nobel
[0249] 1,4-Dichlorobenzene ("DCB") (≥99): obtained from Alfa Aesar
[0250] 1,3-Dichlorobenzene ("mDCB") (≥99): obtained from Alfa Aesar
[0251] Sodium hydroxide (≥97.0%): obtained from Fisher Chemical
[0252] Sodium acetate (≥99%): obtained from VWR Chemicals
[0253] 3,5-Dichloroaniline ("DCA") (98%): obtained from Alfa Aesar
[0254] 1,2,4-Trichlorobenzene ("TCB") (99%): obtained from Alfa Aesar
[0255] 3,3',4,4'-Biphenyltetracarboxylic dianhydride ("BPDA") (97%): obtained from Sigma
[0256] Characterization
[0257] The extrusion rate referred to as "1270ER" is generally measured by the method of ASTM D 1238-86, Procedure B-Automatically Timed Flow Rate Procedure, Condition 316 / 5.0. The diameter of the orifice is 0.0825+ / -0.002 inches and the length is 1.25 inches, a total drive weight including the piston of 1270 grams is used, and the temperature used is 316°C, with a warm-up time of 5 minutes before the measurement. The value of 1270ER is expressed as grams per ten minutes (g / 10min). The extrusion rate referred to as "MFR" is carried out using a die with a total drive weight of 5000g using a 0.0825+ / -0.002 inch orifice and a length of 0.315 inches.
[0258] Molecular weights were determined from amorphous pressed film samples by gel permeation chromatography at 210°C using an Agilent PL220 HT-GPC with 1-chloronaphthalene mobile phase and polystyrene standards.
[0259] Melting points were determined by DSC according to ASTM D3418. The sample was heated to 350°C and held for 5 minutes to eliminate any thermal history, cooled to 30°C, and heated again to 350°C, all at a rate of 20°C / min.
[0260] synthesis
[0261] Example 1 : (2.5mol%DCA / 5mol%mDCB terpolymer)
[0262] Resin Synthesis: A 1-L autoclave reactor was charged with 34.50 g sodium hydroxide (0.863 mol), 22.89 g sodium acetate (0.279 mol), 79.78 g NaSH (59.43 wt%, 0.846 mol), and 234 g NMP. The reactor was purged with nitrogen and pressurized to 10 psig and set to stir continuously at 400 rpm. A separate addition vessel was charged with 115.00 g DCB (0.782 mol), 3.43 g DCA (0.021 mol), 6.22 g mDCB (0.042 mol), and 50 g NMP. The addition vessel was purged with nitrogen and pressurized to 90 psig and heated to 100°C. The reactor was heated from room temperature at 1.5°C / min. Once reaching 150 ℃, the reactor is vented by a condenser, and 46mL of clear condensate is collected under a small nitrogen stream (60mL / min) until the reactor reaches 200 ℃. At this point, remove the condenser, stop the nitrogen stream, and quickly add the DCB / DCA / mDCB / NMP mixture in the addition container to the reactor. Load another 30g NMP into the addition container, purge with nitrogen and pressurize to 90psig, and add the contents to the reactor immediately. The sealed reactor is continued to be heated to 240 ℃ and then kept at 240 ℃ for 2 hours, heated to 265 ℃ with 1.5 ℃ / min, and kept at 265 ℃ for 2 hours. At this point, a mixture of 15.8g water and 7.5g NMP is added to the reactor under 250psig pressure. The reactor contents are then cooled to 200 ℃ with 1.0 ℃ / min, and finally allowed to cool to room temperature. The resulting slurry was diluted with 200 mL of NMP, removed from the reactor, heated to 80° C., and sieved on a No. 120 sieve (125 μm opening). The solid was rinsed with an additional 100 mL of warm NMP (60° C.). The solid was then transferred to a separate container, stirred in 300 mL of heated DI water (70° C.) for 15 minutes, and sieved on a No. 120 sieve, and the process was repeated a total of five times. The rinsed solid was dried in a vacuum oven at 100° C. under nitrogen overnight to give 60.49 g of white granular resin. 1270ER=102 g·(10 min) -1 . M w =27,000 g / mol. m =263℃.
[0263] Reactive extrusion with BPDA to test amine reactivity: 12 g of the polymer obtained as detailed above was mixed with 407 mg BPDA for 10 minutes at a screw speed of 100 rpm and a barrel temperature of 335° C. in a DSM Xplore 15 cc twin screw micro compounder. The resulting yellow-brown extrudate had an MFR of 0, indicating the presence of significant crosslinking; this is further evidence of the presence of bound amine groups in the polymer.
[0264] BPDA (ie 3,3',4,4'-biphenyl-tetracarboxylic dianhydride) was thus demonstrated to form imide crosslinks between amine sites of the obtained polymer, resulting in a significant decrease in the measured melt flow rate (MFR) of the polymer.
[0265] Example 2 : (2.5mol%DCA / 7.5mol%mDCB terpolymer)
[0266] Resin Synthesis: According to the procedure from Example 1, but in a 400-L reactor, 31.23 kg of sodium hydroxide solution (50.40 wt%, 394 mol), 12.13 kg of sodium acetate (148 mol), 41.56 kg of NaSH (56.62 wt%, 420 mol), 53.18 kg of DCB (362 mol), 1.63 kg of DCA (10 mol), 4.43 kg of mDCB (30 mol) and a total of 123.47 kg of NMP were used. The reaction gave 25.17 kg of white powdery resin. 1270ER = 54 g (10 min) -1 . M w =34,000 g / mol. m =258℃.
[0267] Reactive extrusion with BPDA to test amine reactivity: 12 g of the polymer obtained as indicated above was mixed with 407 mg BPDA for 10 minutes at a screw speed of 100 rpm and a barrel temperature of 335° C. in a DSM Xplore 15 cc twin screw micro compounder. The resulting yellow-brown extrudate had an MFR of 21, indicating significant crosslinking; this is further evidence of the presence of bound amine groups in the polymer.
[0268] Example 3 : (2.5mol%DCA / 10mol%mDCB terpolymer)
[0269] Resin synthesis: According to the procedure from Example 1, 33.69 g of sodium hydroxide (0.842 mol), 22.36 g of sodium acetate (0.273 mol), 77.91 g of NaSH (59.43 wt%, 0.826 mol), 106.23 g of DCB (0.723 mol), 3.35 g of DCA (0.021 mol), 12.14 g of mDCB (0.083 mol) and a total of 307 g of NMP were used. The reaction gave 42.78 g of white granular resin. 1270ER = 183 g (10 min) -1 . M w =25,000 g / mol. m =248℃.
[0270] Reactive extrusion with BPDA to test amine reactivity: 12 g of the polymer as indicated above was mixed with 407 mg BPDA at a screw speed of 100 rpm and a barrel temperature of 335° C. for 10 minutes in a DSM Xplore 15cc twin screw micro compounder. The resulting yellow-brown extrudate had an MFR of 0.66, indicating significant crosslinking; this is further evidence of the presence of bound amine groups in the polymer.
[0271] Example 4 : (2.5mol%DCA / 7.5mol%mDCB / 0.8%TCB quaternary polymer)
[0272] Resin synthesis: According to the procedure from Example 1, 31.82 g of sodium hydroxide (0.796 mol), 21.11 g of sodium acetate (0.257 mol), 76.78 g of NaSH (56.95 wt%, 0.780 mol), 103.19 g of DCB (0.702 mol), 3.16 g of DCA (0.019 mol), 8.60 g of mDCB (0.058 mol), 1.132 g of TCB (0.006 mol) and a total of 290 g of NMP were used. The reaction gave 77.17 g of white granular resin. 1270ER = 20 g (10 min) -1 . M w =42,000 g / mol. m =248℃.
[0273] Reactive extrusion with BPDA to test amine reactivity: 12 g of the polymer as indicated above was mixed with 407 mg BPDA at a screw speed of 100 rpm and a barrel temperature of 335° C. for 10 minutes in a DSM Xplore 15 cc twin screw micro compounder. The resulting yellow-brown extrudate had an MFR of 0, indicating significant crosslinking; this is further evidence of the presence of bound amine groups in the polymer.
[0274] Comparative Example 1: (2.5 mol% DCA copolymer)
[0275] Resin Synthesis: According to the procedure from Example 1 (except that the polymer was isolated on a medium porosity sintered funnel instead of on a sieve), 33.40 g of sodium hydroxide (0.835 mol), 22.17 g of sodium acetate (0.270 mol), 80.35 g of NaSH (57.13 wt%, 0.819 mol), 117.35 g of DCB (0.798 mol), 3.32 g of DCA (0.020 mol) and a total of 304 g of NMP were used. The reaction gave 81.9 g of white powdery resin. 1270ER = 147 g (10 min) -1 . M w =23,000 g / mol. m =280℃.
[0276] Reactive extrusion with BPDA to test amine reactivity: 12 g of the polymer as indicated above was mixed with 407 mg BPDA at a screw speed of 100 rpm and a barrel temperature of 335° C. for 10 minutes in a DSM Xplore 15 cc twin screw micro compounder. The resulting yellow-brown extrudate had an MFR of 0.41, indicating significant crosslinking; this is further evidence of the presence of bound amine groups in the polymer.
[0277] Comparative Example 2: (5 mol% DCA copolymer)
[0278] Resin Synthesis: According to the procedure from Example 1 (except that the polymer was isolated on a medium porosity sintered funnel instead of on a sieve), 32.16 g of sodium hydroxide (0.804 mol), 21.34 g of sodium acetate (0.260 mol), 77.35 g of NaSH (57.13 wt%, 0.788 mol), 110.08 g of DCB (0.749 mol), 6.38 g of DCA (0.039 mol) and a total of 293 g of NMP were used. The reaction gave 79.21 g of white powdery resin. 1270ER = 793 g (10 min) -1 . M w =16,000 g / mol. m =276℃.
[0279] Reactive extrusion with BPDA to test amine reactivity: 12 g of the resin was mixed with 810 mg of BPDA for 10 minutes at a screw speed of 100 rpm and a barrel temperature of 335° C. in a DSM Xplore 15 cc twin screw micro compounder. The resulting yellow-brown extrudate had an MFR of 0, indicating significant crosslinking; this is further evidence of the presence of bound amine groups in the polymer.
[0280] Comparative Example 3: (10 mol% DCA copolymer)
[0281] Resin Synthesis: Synthesized according to the procedure from Example 1 (except the polymer was isolated on a medium porosity sintered funnel instead of on a sieve) with 32.29 g sodium hydroxide (0.807 mol), 21.43 g sodium acetate (0.261 mol), 77.67 g NaSH (57.13 wt%, 0.792 mol), 104.71 g DCB (0.712 mol), 12.82 g DCA (0.079 mol) and a total of 294 g NMP. The reaction gave 82.73 g of white powdered resin. 1270ER could not be measured and was >10,000. M w =7,000 g / mol. m =256℃.
[0282] Reactive extrusion with BPDA to test amine reactivity: 12 g of the polymer obtained as indicated above was mixed with 1.61 g of BPDA for 10 minutes at a screw speed of 100 rpm and a barrel temperature of 335° C. in a DSM Xplore 15 cc twin screw micro compounder. The resulting yellow-brown extrudate had an MFR of 0, indicating the presence of significant crosslinking; this is further evidence of the presence of bound amine groups in the polymer.
[0283] DSC data were obtained from amorphous film samples by heating to 350°C, holding for 5 minutes, cooling to 30°C and heating again to 350°C (all at 20°C / min). MFR melt flow index was measured on an extrusion plastometer at 315.6°C using a 5.00 kg weight and a 0.0825 inch x 0.315 inch die. 1270ER melt flow index was measured on an extrusion plastometer at 315.6°C using a 1.27 kg weight and a 0.0825 inch x 1.25 inch die.
Claims
1. A poly(arylene sulfide) polymer [polymer (PAS)] having a weight average molecular weight of at least 24,000 as determined by gel permeation chromatography, said polymer (PAS) comprising: - a repeating unit represented by the following formula (R PASp ): [-Ar p -S-] (R PASp ) in -Ar p -yes The amount thereof is 85.0% to 97.0% by mole; - a repeating unit represented by the following formula (R PASo / m ): [-Ar o / m -S-] (R PASo / m ) in -Ar p / m -yes and Any one of The amount thereof is 2.5% to 10.0% by mole; and - a repeating unit represented by the following formula (R PASn ): [-Ar n -S-] (R PASn ) in -Ar n -yes The amount is 0.5% to 5.0% by mole, in: - mol% is determined relative to the total number of moles of repeating units of the polymer (PAS); -R is independently selected in each case from the group consisting of: C1-C 12 Alkyl, C7-C 24 Alkyl aryl, C7-C 24 Arylalkyl, C6-C 24 Arylene and C6-C 18 aryloxy; - i is in each case an independently selected integer from 0 to 4; -j is in each case an independently selected integer from 0 to 3.
2. The polymer (PAS) according to claim 1, comprising: - a repeating unit (R) in an amount of 85.0 to 97.0 mol% PASp ); - a repeating unit (R) in an amount of 2.5 to 10.0 mol% PASo / m ); - a repeating unit (R) in an amount of 0.5 to 5.0 mol% PASn );as well as, - Optionally, the repeating unit (R PASt ) wherein the mole % is determined relative to the total moles of repeating units of the polymer (PAS); and The polymer (PAS) preferably comprises: - a repeating unit (R) in an amount of 88.0% to 96.0% by mole PASp ); - a repeating unit (R) in an amount of 3.0 to 8.0 mol% PASo / m ); - a repeating unit (R) in an amount of 1.0 to 4.0 mol% PASn );as well as, - Optionally, the repeating unit (R PASt ), wherein the mole % is determined relative to the total moles of repeating units of the polymer (PAS); and The polymer (PAS) more preferably comprises: - a repeating unit (R) in an amount of 89.0% to 94.5% by mole PASp ); - a repeating unit (R) in an amount of 4.0 to 7.5 mol% PASo / m ); - a repeating unit (R) in an amount of 1.5 to 3.5 mol% PASn );as well as, - Optionally, the repeating unit (R PASt ), wherein the mole % is determined relative to the total moles of repeating units of the polymer (PAS).
3. The polymer (PAS) according to claim 1 or 2, wherein the polymer (PAS) further comprises a repeating unit (R PASt ): [-Ar t -S-] (R PASt ) Among them -Ar t -yes in: -R is independently selected in each case from the group consisting of: C1-C 12 Alkyl, C7-C 24 Alkyl aryl, C7-C 24 Arylalkyl, C6-C 24 Arylene and C6-C 18 aryloxy; - k is in each case an independently selected integer from 0 to 3; -m is 1 or 0 in each case.
4. The polymer (PAS) according to claim 3, wherein The polymer (PAS) comprises: - a repeating unit (R) in an amount of 85.0% to 96.8% by mole PASp ); - a repeating unit (R) in an amount of 2.5 to 10.0 mol% PASo / m ); - a repeating unit (R) in an amount of 0.5 to 5.0 mol% PASn );as well as, - a repeating unit (R) in an amount of 0.2 to 3.0 mol% PASt ) wherein the mole % is determined relative to the total moles of repeating units of the polymer (PAS); and Preferably, the polymer (PAS) comprises: - a repeating unit (R) in an amount of 88.0% to 95.7% by mole PASp ); - a repeating unit (R) in an amount of 3.0 to 8.0 mol% PASo / m ); - a repeating unit (R) in an amount of 1.0 to 4.0 mol% PASn );as well as, - a repeating unit (R) in an amount of 0.3 to 2.0 mol% PASt ), wherein the mole % is determined relative to the total moles of repeating units of the polymer (PAS); and Wherein more preferably, the polymer (PAS) comprises: - a repeating unit (R) in an amount of 89.0% to 94.0% by mole PASp ); - a repeating unit (R) in an amount of 4.0 to 7.5 mol% PASo / m ); - a repeating unit (R) in an amount of 1.5 to 3.5 mol% PASn );as well as, - a repeating unit (R) in an amount of 0.5 to 1.5 mol% PASt ), wherein the mole % is determined relative to the total moles of repeating units of the polymer (PAS).
5. A polymer (PAS) according to any one of the preceding claims, wherein The polymer (PAS) consists of or consists essentially of repeating units (R PASp )、(R PASo / m )、(R PASn ) and optionally (R PASt ), or the polymer (PAS) consists of or consists essentially of the repeating unit (R PASp )、(R PASo / m )、(R PASn ) and (R PASt )composition.
6. A polymer (PAS) according to any one of the preceding claims, wherein: -Repeating unit (R PASp ) is a repeating unit having the formula (R PPSp ): and / or -Repeating unit (R PASo / m ) is selected from repeating units having the formula (R PPSo ) and (R PPSm ) group: and / or -Repeating unit (R PASn ) is a compound having the formula (R PPSn,o )(R PPSn,m )(R PPSn,p ) in any of the repeating units (R PPSn ): and / or -Repeating unit (R PASn ) is a compound having the formula (R PPS_TCA )'s repeating unit: and / or - When present, the repeating unit (R PASt ) is of the formula: (R PPSt ) repeating unit (R PPSt ), wherein m is 0 or 1, preferably m is 0.
7. A polymer (PAS) according to any one of the preceding claims, - wherein the polymer (PAS) has a weight average molecular weight (M) of at least 25,000 g / mol, more preferably at least 26,000 g / mol, even more preferably at least 27,000 g / mol w ); and / or the polymer (PAS) has a weight average molecular weight (M) of at most 120,000 g / mol, more preferably at most 110,000 g / mol, even more preferably at most 100,000 g / mol, still more preferably at most 90,000 g / mol. w ), where M w Determined by gel permeation chromatography; and / or - wherein the polymer (PAS) has a melting point (T m ); and / or the polymer (PAS) has a melting point (T of at most 265°C, more preferably at most 264°C, even more preferably at most 263°C m ), where T m Determined in a differential scanning calorimeter (DSC) according to ASTM D3418 using a heating and cooling rate of 20°C / min on the 2nd thermal scan.
8. A process for the manufacture of a poly(arylene sulfide) polymer, in particular for the manufacture of a polymer (PAS) according to any one of claims 1 to 7, comprising reacting a monomer mixture comprising: - from 85.0% to 97.0% by mole of at least one compound having the formula X-Ar p -X', wherein -Ar p -yes - from 2.5% to 10.0% by mole of at least one second dihalogenated compound of the formula: X"-Ar o / m -X"', where -Ar o / m -yes and Any one of - from 2.5 to 5.0 mol% of at least one third dihalogenated compound having the formula: X' v -Ar n -X v , where -Ar n -yes in: -X、X'、X”、X”'、X' v and X v each of which is an independently selected halogen, preferably chlorine or bromine, more preferably chlorine; -R is independently selected in each case from the group consisting of: C1-C 12 Alkyl, C7-C 24 Alkyl aryl, C7-C 24 Arylalkyl, C6-C 24 Arylene and C6-C 18 aryloxy; - i is in each case an independently selected integer from 0 to 4; -j is in each case an independently selected integer from 0 to 3.
9. The method according to claim 8, in, The compound having the formula X-Ar p -The first dihalogenated compound of X' is p-dihalobenzene, preferably p-dichlorobenzene; and / or Wherein, the compound has the formula X"-Ar o / m -X"'s second dihalogenated compound is selected from the group consisting of o-dihalobenzene and m-dihalobenzene; and preferably selected from the group consisting of o-dichlorobenzene and m-dichlorobenzene; and / or Among them, the formula is: X' v -Ar n -X v The third dihalogenated compound is a dihaloaniline, and is preferably selected from the group consisting of 3,5-dichloroaniline, 2,5-dichloroaniline and 2,6-dichloroaniline, wherein 3,5-dichloroaniline is even more preferred; and / or wherein the trihalogenated compound having formula (II) is a trihalobenzene, more preferably 1,2,4-trichlorobenzene.
10. The method according to claim 8 or 9, wherein: The compound (SC) is selected from the group consisting of thiosulfates, thioureas, thioamides, elemental sulfur, thiocarbamates, metal disulfides and oxysulfides, thiocarbonates, organic mercaptans, organic mercaptoxides, organic sulfides, alkali metal sulfides and disulfides, and hydrogen sulfide; and the compound (SC) is preferably an alkali metal sulfide, in particular an alkali metal sulfide generated in situ from an alkali metal hydrosulfide and an alkali metal hydroxide; and the compound (SC) is most preferably NaS generated in situ from NaSH and NaOH.
11. The process according to any one of claims 8 to 10, wherein the reaction of compound (SC) with the monomer mixture takes place in a polar aprotic solvent, preferably selected from the group consisting of hexamethylphosphoramide, tetramethylurea, N,N-ethylenedipyrrolidone, N-methyl-2-pyrrolidone ("NMP"), pyrrolidone, caprolactam, N-ethylcaprolactam, sulfolane, N,N'-dimethylacetamide and 1,3-dimethyl-2-imidazolidinone.
12. A composition (C) comprising a polymer (PAS) according to any one of claims 1 to 7 and at least one epoxy resin.
13. The composition (C) according to claim 12, wherein The epoxy resin is selected from the group consisting of: - epoxy ethers formed by reaction of epihalohydrins such as epichlorohydrin, for example with polyphenols, typically and preferably in the presence of a base, wherein the polyphenols include catechol, hydroquinone, resorcinol, bis(4-hydroxyphenyl)-2,2-propane (bisphenol A), bis(4-hydroxyphenyl)-1,1-isobutane, bis(4-hydroxyphenyl)-1,1-ethane, bis(2-hydroxyphenyl)-methane, 4,4-dihydroxybenzophenone, 1,5-hydroxynaphthalene; - polyglycidyl ethers of polyols derived from polyols including ethylene glycol, propylene glycol, butanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, glycerol, trimethylolpropane, pentaerythritol, and polyglycidyl esters of polycarboxylic acids formed by the reaction of epihalohydrins or other epoxy compositions with aliphatic or aromatic polycarboxylic acids including succinic acid, adipic acid, azelaic acid, sebacic acid, maleic acid, fumaric acid, phthalic acid, tetrahydrophthalic acid, hexahydrophthalic acid, trimellitic acid; - Epoxy resins derived from the oxidation of ethylenically unsaturated alicyclic compounds; - Epoxy novolac resins obtained by the reaction of epihalohydrins with condensation products of aldehydes and monohydric or polyhydric phenols.
14. The composition according to claim 12 or 13, wherein The composition (C) further comprises at least one curing agent, which is preferably selected from the group consisting of dihydrazides prepared by the reaction of carboxylic acid esters with hydrazine hydrate, preferably including carbodihydrazide, oxalic acid dihydrazide, malonic acid dihydrazide, ethylmalonic acid dihydrazide, succinic acid dihydrazide, glutaric acid dihydrazide, adipic acid dihydrazide, pimelic acid dihydrazide, sebacic acid dihydrazide, maleic acid dihydrazide, isophthalic acid dihydrazide, eicosanedioic acid dihydrazide, valine dihydrazide and mixtures thereof.
15. A method for coating a substrate with a composition (C) according to any one of claims 12 to 14.